2014
DOI: 10.1093/mnras/stu708
|View full text |Cite
|
Sign up to set email alerts
|

A state change in the low-mass X-ray binary XSS J12270−4859

Abstract: Millisecond radio pulsars acquire their rapid rotation rates through mass and angular momentum transfer in a low-mass X-ray binary system. Recent studies of PSR J1824−2452I and PSR J1023+0038 have observationally demonstrated this link, and they have also shown that such systems can repeatedly transition back-and-forth between the radio millisecond pulsar and low-mass X-ray binary states. This also suggests that a fraction of such systems are not newly born radio millisecond pulsars but are rather suspended in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
240
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(255 citation statements)
references
References 36 publications
12
240
1
Order By: Relevance
“…Of course, since the discovery of the first eclipsing pulsars we know of systems where mass transfer (loss from the companion) occurs with no accretion onto the neutron star, however this is an unlikely scenario for the binary at hand. Although, perhaps, at some point in time the pulsar could turn on in the radio, (i.e., become a radio pulsar if the mass transfer rate temporarily drops) as predicted theoretically (Kluźniak et al 1988) and recently observed (e.g., Archibald et al 2009;Bassa et al 2014), it would take a very powerful radio pulsar indeed to expel from the system matter transferred at such a prodigious rate. Note that the known eclipsing pulsars that ablate their companions are in fact millisecond pulsars, and their companions have fairly low masses.…”
Section: An Ultraluminous Accreting Millisecond Pulsarmentioning
confidence: 68%
“…Of course, since the discovery of the first eclipsing pulsars we know of systems where mass transfer (loss from the companion) occurs with no accretion onto the neutron star, however this is an unlikely scenario for the binary at hand. Although, perhaps, at some point in time the pulsar could turn on in the radio, (i.e., become a radio pulsar if the mass transfer rate temporarily drops) as predicted theoretically (Kluźniak et al 1988) and recently observed (e.g., Archibald et al 2009;Bassa et al 2014), it would take a very powerful radio pulsar indeed to expel from the system matter transferred at such a prodigious rate. Note that the known eclipsing pulsars that ablate their companions are in fact millisecond pulsars, and their companions have fairly low masses.…”
Section: An Ultraluminous Accreting Millisecond Pulsarmentioning
confidence: 68%
“…In this case the magnetosphere should be devoid of matter and the radio pulsar mechanism should turn on with a strong pulsar wind preventing further accretion (see e.g., Stella et al 1994;Burderi et al 2001). This is what is currently thought to occur in the radio-pulsar phase of the three transitional pulsars recently discovered (Archibald et al 2009;Papitto et al 2013;Bassa et al 2014;Patruno et al 2014;Roy et al 2014Roy et al , 2015Stappers et al 2014) and in the quiescence phase of SAX J1808.4−3658 (Homer et al 2001;Burderi et al 2003;). The fact that in SAX J1808.4 −3658 the X-ray luminosity increases by three orders of magnitude right after reaching the luminosity minima on a very fast timescale of 1-2 days (see Figures 2 and 3) suggests that the radio pulsar mechanism does not turn on, although a very rapid switch cannot be excluded at the moment.…”
Section: Accretion Flow Geometrymentioning
confidence: 96%
“…A similar system is the LMXB XSS J12270−4859. In recent years, radio, optical, and X-ray observations of this system suggested that, since the end of 2012, it may have switched to a MSP phase (Bassa et al 2014;Bogdanov et al 2014;de Martino et al 2015), and the detection of 1.69 ms radio pulsations provided compelling evidence for the change of state (Roy et al 2014). …”
Section: Based On Observations Made With European Southern Observatormentioning
confidence: 97%
“…The system remained stable in gamma rays, X-rays, and optical wavelengths for about a decade until 2012 November/December, when a substantial decline in brightness in all of these bands was reported (Bassa et al 2013;Tam et al 2013;Bassa et al 2014;Bogdanov et al 2014). This variability reinforced the prediction, first made by Hill et al (2011), that the system could harbour an active radio MSP, sharing similar properties with J1023.…”
Section: Xss J12270-4859mentioning
confidence: 97%